Sistem Pendukung Keputusan Menentukan Pemutusan Hubungan Kerja Karyawan CV. Biring Ndu Cahaya Panglong Dengan Metode AHP - Eko Lianto Damanik; R Mahdalena Simanjorang (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
CV Biring Ndu Cahaya Panglong is a company that sells various types of building materials and equipment, located in Tanah Merah village, Dusun II Pendukuan, Galang District. Currently CV. Biring Ndu Cahaya Panglong does not have an information system that is able to assist in managing employee data. The employee data includes all data related to employee control activities. The AHP method is one of the methods in decision support systems that is unique compared to the others. There are 10 alternative names and 5 criteria in determining layoffs, namely negligence in work (C1), absenteeism (C2), theft of goods (C3), not neat (C4), spreading company disgrace (C5). The results obtained from this study with the highest score is Arya Sinaga with a value of 0.272 which indicates that the alternative with the highest ranking will be dismissed from work.